Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan Di Desa Padasari Kecamatan Cimalaka Kabupaten Sumedang - Willya Achmad; Siti Sofro Sidiq; R. Yogie Prawira (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the factors that cause poverty in Padasari Village, Cimalaka District, and Sumedang Regency, separately or simultaneously. This research uses quantitative methods with multiple descriptive and linear approaches. Determination of the sample in this study using the Slovin model. Data processing techniques are carried out through validity and reliability tests. Data were analyzed using the SPSS application. The results of the study show that if not adequately managed, natural resources can have a negative impact on poverty levels, human resources involve the quality and quantity of a region's workforce, and human resources who do not have access to education, skills, and training will be difficult for them to obtain welfare.